RECENT RESEARCH IN MANAGEMENT, ACCOUNTING AND ECONOMICS (RRMAE) - Hafinaz, Dr; R., Hariharan; Kumar, R. Senthil (ROUTLEDGE, 2025)
The conference brought together innovative academics and industrial experts to present novel contributions related to real-world aspects of Economics, Management and Accounting. The primary goal of the conference was to promote research and developmental activities in these three fields. Another goal was to promote scientific information interchange between researchers, developers, engineers, students, and practitioners working in and around the world.
Keywords: Economic development -- Congresses.; Management -- Congresses.; Accounting -- Congresses.; elektronické knihy; electronic books